A fed-batch feeding with succinic acid strategy for astaxanthin and lipid hyper-production in Haematococcus pluviualis. (November 2021) - Yu, Chunli; Wang, Hui-Ping; Qiao, Tengsheng; Zhao, Yongteng; Yu, Xuya
Graphical abstract: Highlights: Succinic acid fed-batch strategy increases biomass, astaxanthin and lipid yields. Succinic acid upregulates astaxanthin and lipids biosynthetic genes levels. Succinic acid improves reactive oxygen species levels and antioxidase activities. Abstract: Effects of succinic acid (SA) in fed-batch feeding mode on astaxanthin and lipids biopoduction of Haematococcus pluvialis against abiotic stresses were explored. By comparison with the control, the initial addition of SA on day 0 increased the production of astaxanthin by 71.61%. More importantly, the maximum values of astaxanthin (35.88 mg g −1 ) and lipid (54.79%) contents were obtained after supplementation of SA on day 7. Meanwhile, under SA treatment, the chlorophyll, carbohydrate, and protein levels were reduced, but the intracellular levels of SA and reactive oxygen species (ROS), the transcription levels of astaxanthin and fatty acids biosynthesis-, and antioxidant system-related genes were increased. Furthermore, scaling-up cultivation in bioreactor further enhanced the astaxanthin productivity from H. pluvialis . Generally, this study proved the intermittent SA feeding method in fed-batch culture as a potent strategy that facilitated massive astaxanthin and lipids production in algae.